Smart Strategies and Solutions for Managing MSME Cash Flow to Achieve Business Stability and Growth in MSMEs of Paninggilan, Paninggilan Village, South Tangerang, Banten - Diah Kurniasih; Winursito Winursito; Rizki Cahayasari; Lukman Anthoni; Firman Tatariyanto (Abdimas Paspama, 2025)
This community service program aimed to enhance cash flow management capabilities among MSMEs in Paninggilan, South Tangerang. Through participatory training and mentoring, MSME owners were equipped with knowledge and tools to manage financial transactions, monitor cash flows, and utilize digital financial applications. Post-training evaluations indicated significant improvements in financial literacy, receivables management practices, and technology adoption among participants. The introduction of simple fintech tools enabled faster and more accurate financial decision-making, while structured payment strategies reduced liquidity risks. However, challenges such as digital resistance and access barriers to formal financing were identified, highlighting the need for ongoing support. Overall, the program successfully strengthened the financial resilience of MSMEs and contributed to promoting business stability and growth. Continuous mentoring and collaboration with financial institutions are recommended to sustain and amplify the program’s impact on MSME development in the post-pandemic economic recovery era.